Some effects of phosphorus (P) and potassium and residual P and K fertilizer on the growth of Pinus patula at Usutu, Swaziland - Crous, Jacob W. (My University, 2009)
The sustainable production of renewable timber resources is not only important to Sappi and other forestry companies to produce pulp, paper and timber profitably, but to society in general to maintain or improve living standards in an ecological friendly manner. Research on the sustained production from short rotations of P. patula on the Usutu plantation has shown that operational application of P and K fertilizer corrected the 20% growth decline that was observed between first and second rotations on about 13% of the plantation that consists of soils derived from gabbro lithology. However, additional trials were established to investigate the magnitude and duration of responses from the application of different amounts of P and K fertilizer at different times of stand development. Results from two of these practical trials are reported here. Trial R155, a phosphorus (P) by potassium (K) by weed control trial was established to determine the optimum application rate and timing of PK fertilizer. The P and K fertilizer were applied in three amounts, 20/20, 40/40 and 80/80 kg P ha-1 and K ha-1. The 40/40 and 80/80 amounts were applied with three different regimes, either applying all of the fertilizer at planting or after pruning (5 years), or splitting the application into a 20/20 application at planting (spot application) and applying the remaining fertilizer at pruning (either 20 or 60 kg of P and K by broadcast application). At cleafelling age (15 years) topsoil (0-100 mm), forest floor litter, stemwood, stembark and foliar samples were collected and chemically analysed to determine the impact of PK fertilization on the nutrient content thereof at rotation age. The fate of the K fertilizer was determined by applying the Rb/K reverse tracer technique, whereby the amount of Rb in the plants was related to the naturally occurring Rb in the soil and used as a “tag” of native soil-K. Tree survival was not affected by the application of the PK fertilizer. However, the PK fertilizer reduced the coefficient of variation in DBH from 23% to 20%. The application of 80/80 kg P and K per hectare increased DBH from 20.0 to 23.0 cm; tree height from 19.6 to 20.4 m; and volume production by 83 m³ ha-1 (29%). However, the application of 80/80 fertilizer decreased basic wood density by 3% from 0.372 to 0.361 g cm-3. The positive volume growth response was not offset by the slight decrease in timber density as 28 t ha-1 (26%) more fibre was produced. The effect of P fertilizer was more pronounced at the end of the rotation than the effect of K fertilizer. Compared to the control the application of 80/80 PK fertilizer increased the concentration of plant available P (Bray II) in the first 100 mm of the topsoil from 3 mg kg-1 to 12 mg kg-1 and increased the foliar P level significantly to 0.13%. The foliar P level as well as the concentration of plant available P in the topsoil increased when the fertilizer was applied closer to rotation age. The split application of either 40/40 or 80/80 PK fertilizer increased the stemwood P concentration by 50%, compared to the 23 mg kg-1 P that was found on the control plots. Application of the 40/40 and 80/80 amounts of fertilizer increased the mass of the forest floor litter layer by 27 300 kg ha-1 (35%) compared to the control. The P and K content (kg ha-1) in the forest floor litter layer, stemwood and stembark were significantly greater on the fertilized plots. Results from the Rb/K reverse tracer technique showed that none of the applied K remained in the soil at the end of the rotation. In the forest floor litter, 4% of the fertilizer K was found on plots where 80/80 P and K were applied. The results confirmed that within the various plant components fertilizer K contributed more to the amount of K in the wood (28.7%) than to the amount of K in the bark (19.5%) or the foliage (8.5%). In trial R128, a long-term phosphorus (P) and potassium (K) fertilizer trial, established on abbro-derived soil, the growth and foliar nutrient response of six-year-old P. patula as well as the chemical changes that occurred within the topsoil and forest floor litter were studied in the presence and absence of previously applied (residual) fertilizer. In 1989, when the third rotation (3R) trees were six years old, 75 kg elemental P and K per ha, respectively, was applied to one half of 52 plots as a foundation for a factorial design with applications of 0, 25 and 50 kg P and K per ha, which was superimposed on the 3R trial plots in the following fourth rotation (4R). The 50 kg ha-1 applications consisted of two applications of 25 kg ha-1, the first as a spot application at planting in 1999 and the second as a broadcast application after pruning at age 5 years in 2004. Fifteen years after the initial fertilizer application, 41 kg ha-1 more 0.5 M H2SO4 extracted Pinorganic + Porganic was found in the topsoil of the fertilised plots than in the control plots. The residual fertilizer increased the P concentration of the various needle components and had no effect on any other components or nutrients in the organic matter. Furthermore, the results indicated that in the presence of residual fertilizer, the reapplication of only K fertilizer increased volume by 27 m³ ha-1 (21.5%) at age seven years. This was statistically similar to the 25.2 m³ ha-1 (20%) increase from a combined PK application. The maximum volume increment over a two year period following post v pruning fertilization was achieved when the foliar nutrient concentrations of both nutrients were above the values of 0.14% for P and 0.50% for K, respectively. The combined results supported the current fertilizer prescription to apply P and K fertilizer to previously unfertilized stands. The changes in nutrient concentration and basic wood density with tree height showed the importance to sample at more than one height to obtain an accurate average or total value for each tree. The results from the present study suggested that increased production will lead to increased nutrient removal, threatening long-term site productivity unless both P and K fertilizer are applied to gabbro-derived soils, which have not received any PK fertilizer application previously. A greater proportion of the K nutrient pool compared to the P nutrient pool was removed from the site during harvesting. The residual fertilizer effects highlighted the importance of knowing the fertilizer application history of a site when new fertilizer trials are established. Furthermore, the results indicated that enough residual P fertilizer remained available to supply the early P demand of the next crop, suggesting that the amount of P fertilizer applied to successive rotations can be reduced. Thus, the re-application of inorganic K fertilizer to the subsequent rotations and conservation of organic material to ensure long-term P cycling will be of utmost importance to produce timber sustainably on the gabbro-derived soils at Usutu. The foliar values for P and K as well as the respective nutrient ratios can be used to monitor the responses to the revised fertilizer prescriptions.